A new species of Nactus gecko from boulder-pile habitat on Dauan Island, Torres Strait, Australia - Hoskin, Conrad J.; Davies, Alexander; Aland, Kieran (Zootaxa, 2024)
The Torres Strait Islands lie between Cape York Peninsula, north-east Australia, and the southern coast of Papua New Guinea. The vertebrate fauna of these islands is a relatively depauperate mix of Australian and New Guinean species, with only two endemic species described to date. Here we describe a new species of Nactus gecko discovered during a targeted survey of Dauan Island in the northern Torres Strait. Nactus simakal sp. nov. is a genetically (ND2 mtDNA) and morphologically highly distinct species, with a banded pattern and a slender, elongate form. It is saxicoline, living on deeply piled boulder habitat, and is likely to be restricted to Dauan Island. Nactus simakal sp. nov. is currently known from a very small area and further surveys, and assessment of current and potential threats, are required to assess the conservation status of this species. Nactus simakal sp. nov. is similar in general appearance to N. galgajuga (Ingram, 1978), which is restricted to boulder-pile habitat 750 km to the south in mainland north-east Queensland but is readily distinguished from that species morphologically and genetically.